Improved Flexibility and Economics of Combined Cycles by Power to Gas - Bailera, Manuel; Peña, Begoña; Lisbona, Pilar; Romeo, Luis M. (Frontiers in Energy Research, 2020)
Massive penetration of renewable energy in the energy systems is required to comply with existing CO2 regulations. Considering current power pools, large shares of renewable energy sources imply strong efficiency and economic penalties in fossil fuel power plants as they are mainly operated to regulate the system and constant shutdowns are expected. Under this framework, the integration of a combined cycle power plant (CCPP) with an energy storage technology such as power to gas (PtG) is proposed to virtually reduce its minimum complaint load through the diversion of instantaneous excess electricity. Power to gas produces hydrogen through water electrolysis, which is later combined with CO2 to produce methane. The main novelty of this study relies in the improved flexibility and economics of combined cycles by means of using power to gas as a tool to reduce the minimum complaint load. The principal objective of the study is the quantification of cost reduction under different scenarios of shutdowns and conventional start-ups. The case study analyses a combined cycle of 400 MWe gross power with a minimum complaint load of 30% that can be virtually reduced to 20% by means of a 40- MWe power-to-gas plant. Eight scenarios are defined to compare the reference case of conventional operation under hot, warm, and cold start-ups with power-to-gas-assisted operation. Additionally, PtG-assisted operation scenarios are analyzed with different loads (30–50–70%). These scenarios also include the consideration of a temporary peak of demand occurring in a period in which dispatch is below the minimum complaint load. Under this situation, the response time of conventional plants is very limited, while PtG-assisted CCPP can rapidly satisfy the peak. The techno-economic model quantifies the required fuel, gross and net power, and emissions as well as total costs and incomes under each scenario and net differential profit in an hourly basis. The analysis of the obtained results does not recommend the operation of the PtG-assisted CCPP at minimum complaint load for hot, warm, or cold start-ups. However, important marginal profits are achieved with the proposed system for part-loads operation over 50% for every sort of start-up, avoiding shutdowns and extending the capacity factor.